TO OBSERVE THE HEPATOTOXICITY WITH ANTI-TUBERCULOSIS DRUGS AND ITS FREQUENCY AND SEVERITY - Atif Ahmed1, Mohammad Amjad Kalhoro2, Kuldeep Poorani3, Nisar Ahmed Khokar4, Safia Bano5,Saeed ur Raseed Nazir6. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
OBJECTIVE: To measure the frequency and severity of hepatotoxicity caused by various antituberculosis drugs (ATTs). Study design: prospective cohort study. PLACE AND DURATION: In the Medicine ward of Bilawal Medical College Hospital Kotri one-year duration from April 2019 to April 2020. METHOD: A total of 450 patients with active tuberculosis infection with normal clinical and biochemical liver function were observed. Data were collected and patients were treated with isoniazid, rifampin, Ethambutol and pyrazinamide. The time after the imbalance, if any, in the function was calculated and the time required for regulation was calculated. Treatment was changed if necessary, except for harmful drugs. RESULTS: There were 230 (51.11%) male and 220 (48.88%) female patients. The ages of the patients ranged from 14 to 76, with an average age of 38. The preliminary biochemical estimate showed 6.15 to 12.6 g of hemoglobin, 25 to 59 IU of SGPT, and 100 to 250 mg of serum cholesterol. There were nine patients with alcohol dependence, and almost all subjects used paracetamol for various purposes. During the study period, 86 (19.11%) of 450 people using anti-tuberculosis drugs developed hepatotoxicity determined by clinical studies and by LFTS. All of these patients differed in SGOT and SGPT. The patients had severe impairments in SGOT and SGPT. Women were 22.72% (50 out of 220) more than men (44 out of 230) 19.19%. Due to the hepatotoxicity caused by ATT, elderly patients are relatively more affected than the younger age group. The time elapsed from the start of treatment to the onset of hepatotoxicity has been documented. The maximum number of patients caused hepatotoxicity at the start of treatment 14 days. While 29 patients developed liver failure within 2-4 weeks, the remaining patients developed abnormalities after one month of treatment. Liver function tests normalized in approximately four-fifths of the patients over two weeks. The main culprit was isoniazid 60 (69.76%) followed by pyrazinamide, p <0.01]. CONCLUSION: Antituberculus therapy induced hepatitis is very common and has serious effects of hepatotoxicity in patients.